Astronomical and geographical model for programming microcontrollers of ground-based trackers - Valentyn Ivanitsky; Myhajlo Ryaboschuk; Stoika Myroslav; Serhij Tiutiunnykov; Sztojka Miroszláv; Валентин Іваницький; Михайло Рябощук; Стойка Мирослав; Сергій Тютюнников (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2021)
Abstract. The prospects of using autonomous automatic solar orientation systems to increase the efficiency of small solar power stations are shown. A simple clear astronomical geographical model has been created to develop an algorithm for programming microcontrollers of autonomous trackers for an arbitrary point of the globe. The model is based on the geometric parameters of the Sun trajectory in the celestial sphere. The necessity of establishing the exact local solar time of the point of the power station location to achieve the maximum efficiency of its operation is shown.
Keywords: resource-saving energy; ground-based trackers; solar orientation systems; erőforrás-megtakarító energia; földi nyomkövetők; napenergia-orientációs rendszerek; ресурсозберігаюча енергія; наземні трекери; системи сонячної орієнтації